Asymmetric Enzymatic Hydration of Hydroxystyrene Derivatives1. Issue 8 (17th January 2013) - Wuensch, Christiane; Gross, Johannes; Steinkellner, Georg; Gruber, Karl; Glueck, Silvia M.; Faber, Kurt
<x xml:space="preserve">Abstract</x> More than one activity: Owing to their hydratase activity, phenolic acid decarboxylases catalyze the regio‐ and stereoselective addition of H2O across the CC double bond of hydroxystyrene derivatives yielding (S)‐4‐(1‐hydroxyethyl)phenols with up to 82 % conversion and 71 % ee. Based on structure analysis and molecular docking simulations, a catalytic mechanism for this novel enzymatic reaction is proposed.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>